KETERAMPILAN BERTANYA PADA ANAK USIA 3 TAHUN (KAJIAN PSIKOLINGUISTIK) - Ayu Indah Puspitasari; Salsabila Putri, Tiara (Jurnal PENEROKA, 2024)
The aim of this study is to describe the forms of question sentence types and the factors that influence 3-year-old children with psycholinguistic studies. The subjects of this research are 3-year-old children with male initials A and female initials B. The method used in this research is descriptive qualitative method with observation, listening, recording and classification techniques. The method used in this research is descriptive qualitative method with observation, listening, note taking and classification techniques. The data in this research is in the form of utterances in the form of question sentences from 3 year old children. The results of this study show that 3-year-old children are able to produce question sentences with sentence types that include 1) question sentences with the correct type of question words and intonation; 2) question sentences with the correct type of question words and no intonation; 3) question sentences with intonation and the wrong type of question words; 4) question sentences without intonation and the wrong type of question words; and 5) question sentences with question words ending in -kah. In line with this, there are factors that influence children's questioning skills, namely internal factors and external factors.